Análise do tempo em dinâmicas imersivas de codesign - Arena, Bárbara Winckler (Universidade do Vale do Rio dos Sinos, 2019)
The present research seeks to understand how time expresses and relates in the context of immersive codesign dynamics. The motivation comes from the need for a critical reflection of time and design in the face of the popularization of codesign dynamics and their frequent association with a logic of innovation linked to a culture of acceleration. The methodological conduction is based on the sociology of time for fieldwork analysis, which consisted of observations of three immersive dynamics and interviews with five designers. The analysis identifies temporal patterns expressed in the dynamics processes, categorized in concepts of temporalities. Still, the relationship between these times and the actors involved, both human and nonhuman, is analyzed from the ecology model of social time. With this, immersive dynamics are interpreted as temporal ecosystems, giving light to the social roles played and the temporal powers established in that context. Finally, the ecological perspective of time allows us to problematize the dynamics that overlap with other spheres of social life. The reflections generated by the research serve as both a metadesign input and a critical analysis of the role of design in the time-social perspective.
Keywords: Tempo; Codesign; Imersão; Temporalidades; Time; Codesign; Immersion; Temporalities; ACCNPQ::Ciências Sociais Aplicadas::Desenho Industrial